1996
DOI: 10.1101/lm.2.6.267
|View full text |Cite
|
Sign up to set email alerts
|

7-Nitro indazole, a selective neuronal nitric oxide synthase inhibitor in vivo, impairs spatial learning in the rat.

Abstract: Nitric oxide (NO) is an intercellular messenger that has been suggested to have a role in learning and memory formation. Previous studies with nonselective NO synthase inhibitors have produced contradictory results in learning experiments. However, these drugs also produced blood pressure changes, as NO is an endothelial-derived relaxing factor. A novel NO synthase inhibitor, 7-nitro indazole (7-NI), as a dose (30 mg/kg i.p.) shown previously to inhibit neuronal NO synthase by 85% without affecting blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 51 publications
5
67
0
3
Order By: Relevance
“…In rat amygdala slice recordings, stimulation of guanylate cyclase by YC-1 leads to enhanced and enduring potentiation of the corticoamygdala pathway, and this potentiation could be eliminated by concomitant inhibition of NO synthase by L-NAME (Chien et al, 2003). Other studies have shown in vivo that inhibition of NO synthase impairs memory in rats as assessed by the Morris water maze (Holscher et al, 1996), and recently, Chien et al (2005) have tested YC-1 in vivo and found improvements in Morris water maze performance. Thus, if decreased long-term potentiation in the amygdala is responsible for the behavioral deficits in early separated monkeys, drug treatment with YC-1 may be a promising avenue for future therapeutic intervention.…”
mentioning
confidence: 99%
“…In rat amygdala slice recordings, stimulation of guanylate cyclase by YC-1 leads to enhanced and enduring potentiation of the corticoamygdala pathway, and this potentiation could be eliminated by concomitant inhibition of NO synthase by L-NAME (Chien et al, 2003). Other studies have shown in vivo that inhibition of NO synthase impairs memory in rats as assessed by the Morris water maze (Holscher et al, 1996), and recently, Chien et al (2005) have tested YC-1 in vivo and found improvements in Morris water maze performance. Thus, if decreased long-term potentiation in the amygdala is responsible for the behavioral deficits in early separated monkeys, drug treatment with YC-1 may be a promising avenue for future therapeutic intervention.…”
mentioning
confidence: 99%
“…NOS inhibitors that are more selective for the neuronal isoform are not devoid of adverse effects and may decrease locomotion and/or motor coordination (Dzoljic et al, 1997;Harkin et al, 2003;Mutlu et al, 2011;Ulak et al, 2010;Volke et al, 2003). Moreover 7-NI seems to have a less favourable side-effect profile than TRIM in several paradigms that investigated learning and memory (Holscher et al, 1996;Mutlu et al, 2011;Yildiz Akar et al, 2009;Yildiz Akar et al, 2007;Zou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It was noted, however, that the higher dose did in fact increase mean arterial blood pressure in these rats, indicating that eNOS may also have been inhibited by 7-NI. Administration of 30 mg/kg 7-NI to male rats 30 min prior to training impaired both working and reference memory for a spatial learning task (Hölscher et al 1995), although in another study, administration of either 25 or 50 mg/kg 7-NI to 2-mo-old male rats before training was found to impair only reference memory (Zou et al 1998). Finally, administration of 50 mg/kg 7-NI 1 h prior to passive avoidance training in 1-d-old chicks impaired recall when tested 30 min, 2 h, and 24 h (but not 5 min) later (Hölscher 1994).…”
mentioning
confidence: 99%
“…Administration of 30 mg/kg 7-NI to male rats 30 min prior to training impaired both working and reference memory for a spatial learning task (Hölscher et al 1995), although in another study, administration of either 25 or 50 mg/kg 7-NI to 2-mo-old male rats before training was found to impair only reference memory (Zou et al 1998). Finally, administration of 50 mg/kg 7-NI 1 h prior to passive avoidance training in 1-d-old chicks impaired recall when tested 30 min, 2 h, and 24 h (but not 5 min) later (Hölscher 1994). In the latter study, potential side effects of NOS inhibition on general performance (including motor skills and orientation) were excluded in separate experiments (see also Hölscher et al 1995).…”
mentioning
confidence: 99%